2022
DOI: 10.1039/d2bm00179a
|View full text |Cite
|
Sign up to set email alerts
|

Design, mechanical and degradation requirements of biodegradable metal mesh for pelvic floor reconstruction

Abstract: Pelvic organ prolapse (POP) is the herniation of surrounding tissue and organs into the vagina and or rectum, and is a result of weakening of pelvic floor muscles, connective tissue,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 176 publications
0
9
0
Order By: Relevance
“…The safety zone is intended to stand for maximum stress peaks and is based on a value of 40% strain 30 . However, more recent studies assume maximum strains of 23% which corresponds to the comfort zone 31 . Based on the fiber geometry described, slight changes to the geometry can lead to improved adaptation to the vaginal tissue 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety zone is intended to stand for maximum stress peaks and is based on a value of 40% strain 30 . However, more recent studies assume maximum strains of 23% which corresponds to the comfort zone 31 . Based on the fiber geometry described, slight changes to the geometry can lead to improved adaptation to the vaginal tissue 29 …”
Section: Resultsmentioning
confidence: 99%
“…3D-printed meshes with a wavy fiber geometry are thus optimally suited as surgical meshes for POP not only due to their variable mechanical properties but also due to their large pores with an auxetic dimensional stability in the pores under tensile load, their high effective porosity, their low weight, and the production as monofilament. 31 In this study, our objective and focus were to develop meshes with an auxetic design that show a better deformation behavior during tensile loading due to its negative Poisson ratio. One of the main drawbacks of currently used knitted/woven meshes is the pore collapse and bundling of the fibers under tensile stress leading to a high rate of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-surgical complications can also be related to pore size: when smaller than 1 mm, the risk of infection due to poor tissue ingrowth and fibrotic encapsulation, increases [2,30]. In a previous study, the surgeons suggest a mesh with large pores (>1 mm) avoid pore collapse [31]. Restorelle mesh and the PCL biodegradable printed meshes had a 1.8 and 2.0 mm pore size respectively, which are considered large pore size meshes, thus promoting better tissue ingrowth [32].…”
Section: Discussionmentioning
confidence: 99%
“…Acidity accelerated the degradation of both the XL-fPVA and NaOH-XL-fPVA, which suggested that the section of scaffolds that goes through vaginal walls (i.e., exposed to the acidic virginal environment field [89][90][91] ) should complete the process of degradation first. Neglecting the rapid mass drop in the first several days, the linear regression (Figure S6, Supporting Information) showed that the total degradation would take from ≈8 months (XL-fPVA) to ≈3.7 years (NaOH-XL-fPVA) in such an acidic environment, [96,97] offering high tunability and flexibility for developing individualized medical treatment. In actual implantation, the lifetime of the scaffolds would vary, as the platform may embed with newly grown tissue to provide sufficient support before complete degradation, and the mechanical wear of body movement may also accelerate the process.…”
Section: Biodegradable Propertiesmentioning
confidence: 99%